Selective Synthesis of Double-Layer Nanosheets Via Layered Ruthenic Acid with a Staged Structure - Eda, Tomoya; Muramatsu, Keisuke; Sugimoto, Wataru (Meeting abstracts (Electrochemical Society), 2024)
Noble metal oxide nanosheets are attractive electrode materials owing to their high surface area as well as electrical conductivity and electrochemical stability. Noble metal oxide nanosheets have been studied as materials for electrochemical capacitors and electrocatalysts, focusing on factors such as composition, sheet size, and crystal structure. 1 Noble metal oxide nanosheets are commonly obtained as single-layer nanosheets through exfoliation of pristine layered materials by intercalation of bulky organic species into each interlayer to sufficiently weaken the interactions between layers. Since the properties of nanosheets are modulated according to the number of layers, the selective synthesis of multi-layered nanosheets can be a new strategy for nanosheet-based material design. For selective synthesis of multi-layered nanosheets, site-selective intercalation of layered materials forming superlattices is required. This can limit the interlayers where exfoliation occurs. 2–4 We have previously reported that the dehydration of proton-exchanged layered potassium ruthenate proceeds layer-by-layer, resulting in a stage 2 structure with alternating hydrous and anhydrous interlayers. 5,6 The two types of interlayers in layered ruthenic acid with staged structure should show different reactivity for intercalation because of different degrees of hydration. In this study, we attempted to develop a site-selective intercalation of organic molecules into layered ruthenic acid with staged structure for the selective synthesis of double-layer ruthenic acid nanosheets. Hydrous layered ruthenic acid (Stage 1-HRO) was synthesized by slight modification of previous literature methods. 5,6 Stage 1-HRO was partially dehydrated at a controlled humidity condition to form layered ruthenic acid with staged structure (Stage 2-HRO). The XRD pattern of Stage 2-HRO showed a basal spacing of d = 1.24 nm which is larger than that before dehydration ( d = 0.786 nm). This peak can be attributed to the superlattice structure with alternating hydrous and anhydrous interlayers, suggesting the formation of a stage 2 structure. For ion exchange, Stage-1 HRO and Stage-2 HRO were respectively added to an aqueous solution containing CTA + (cetyltrimethylammonium). The ion exchanged Stage-2 HRO (Stage 2-HRO + CTA + ) shows a larger basal spacing of d = 2.72 nm and its high-order diffractions are visible. The value of d = 2.72 nm is within the range of the anticipated structure when CTA + intercalates only in hydrous interlayers while maintaining a stage 2 structure. The ion exchanged Stage 1-HRO (Stage 1-HRO + CTA + ) shows a basal spacing of d = 2.49 nm, which was smaller than the basal spacing of Stage 2-HRO + CTA + . The ion exchanged samples were dispersed in organic solvent to initiate exfoliation into nanosheets. The height of nanosheets obtained from Stage 1-HRO + CTA + was approximately 1.3 nm, while that obtained from Stage 2-HRO + CTA + was approximately 1.8 nm. Since the crystallographic thickness of single-layered ruthenic acid nanosheets was approximately 0.5 nm, the difference in thickness is consistent with single-layer ruthenic oxide sheets. Considering the presence of CTA + on the surface of nanosheets, double-layer ruthenic oxide nanosheets were exfoliated from Stage 2-HRO + CTA + . These results suggest that preparation of double-layer ruthenium oxide nanosheets is facilitated by controlling the interlayer environment of layered ruthenic acid utilizing the staging phenomenon. References W. Sugimoto and D. Takimoto, Chem. Lett. , 50 , 1304 (2021). T. Nakato, D. Sakamoto, K. Kuroda and C. Kato, Bull. Chem. Soc. Jpn. , 65 , 322 (1992). M. Stöter, B. Biersack, S. Rosenfeldt, M. J. Leitl, H. Kalo, R. Schobert, H. Yersin, G. A. Ozin, S. Förster and J. Breu, Angew. Chem. Int. Ed. , 54 , 4963 (2015). F. Chen, W. Zhou, L. Jia, X. Liu, T. Sasaki and R. Ma, Chem Catal. , 2 , 867 (2022). W. Sugimoto, H. Iwata, Y. Yasunaga, Y. Murakami and Y. Takasu, Angew. Chem. Int. Ed. , 42 , 4092 (2003). K. Fukuda, H. Kato, J. Sato, W. Sugimoto and Y. Takasu, J. Solid State Chem. , 182 , 2997 (2009). Z. Hu, G. He, Y. Liu, C. Dong, X. Wu and W. Zhao, Appl. Clay Sci. , 75 – 76 , 134 (2013). Figure 1